Optimizing Food Waste Decomposition through pH, Moisture Content, and Temperature Control: A Comprehensive Study - Anayet, Abila Hena; Hamzah, Meor Mohammad Hilmi Bin; Mohamed Najib, Mohamed Zuhaili (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2024)
Composting, a crucial process in sustainable waste management, transforms organic matter into nutrient-rich compost, which is an organic byproduct of the decomposition process known as composting. Compost serves as a sustainable means of recycling various organic materials into a nutrient-rich soil conditioner, finding applications in gardens, landscaping, horticulture, urban agriculture, and organic farming. This paper investigated the complex factors affecting the maturity of compost, focusing on parameters such as temperature, pH, and moisture content. The breakdown rates of eight carefully regulated combinations were compared to a sample that had not been altered. The analytic results showed the volume loss over time was a critical component in determining the maturity of compost. Combinations two (Temperature=High, Moisture Content=High, pH=Low), three (Temperature=High, Moisture Content=Low, pH=High), and four (Temperature=High, Moisture Content=Low, pH=Low) showed the most percentage volume loss by day 46, indicating faster maturation compared to the uncontrolled group. In this volume loss comparison, the circular truncated cone formula played a crucial role in revealing the ideal combinations for compost maturation. This comprehensive study not only contributed valuable insights into optimizing composting conditions but also highlighted the diverse applications of compost. By examining the complex interactions between pH, moisture content, and temperature, this study enhanced our knowledge of sustainable waste-to-resource operations and effective composting techniques.